1988
DOI: 10.1099/00221287-134-6-1611
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning of a Gene Affecting the Autolysin Level and Flagellation in Bacillus subtilis

Abstract: A 2.8 kb PstI fragment of Bacillus subtilis 168W DNA has been cloned into Escherichia coli HBlOl and B. subtilis AG5 using pAC3 as a shuttle plasmid. The new plasmid (pBRGl), of 10.2 kb, complemented _PaD mutations which show reduced production of autolysin(s), filamentation and non-motility (deficiency of flagella). Deletion experiments showed that the suppressive gene is located between the Hind111 and XbaI sites (1.0 kb apart) in pBRG 1. The integration of a plasmid having chloramphenicol resistance closely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
37
0

Year Published

1990
1990
1998
1998

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 39 publications
2
37
0
Order By: Relevance
“…Some mutations of these factors [e.g., sacU(Hy) and sin (flaD, lyt)] cause an increase in the expression of extracellular enzymes (2,6,11,12,47,50) and a decrease in the amount of autolysin(s) (6,9,45,46). In this report, we present evidence that the sin (flaDI) mutation greatly reduces expression of the cwlB operon at the transcriptional level.…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…Some mutations of these factors [e.g., sacU(Hy) and sin (flaD, lyt)] cause an increase in the expression of extracellular enzymes (2,6,11,12,47,50) and a decrease in the amount of autolysin(s) (6,9,45,46). In this report, we present evidence that the sin (flaDI) mutation greatly reduces expression of the cwlB operon at the transcriptional level.…”
Section: Discussionsupporting
confidence: 48%
“…pMC1871 DNA was digested with SmaI and Sall, and a 3.1-kb SmaI (blunt-ended)-SalI fragment containing the 3-galactosidase gene was recovered by using Gene Clean. These two fragments and Sail-digested pUD1 DNA (45) were ligated and then used to transform E. coli competent cells. The resultant sigD-lacZ translational fusion plasmid (pSD3), an integrative vector for B. subtilis, is shown in Fig.…”
Section: Materuils and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work has shown that SinR is a repressor of aprE, the gene coding for the secreted protease, subtilisin, and it also inhibits sporulation (Gaur et al 1986 It has recently been shown that SinR exerts its repressive effects on sporulation immediately before stage II, by inhibiting the expression of spolIA, spolIE, and spoHG (Mandic-Mulec et al 1992}. On the other hand, null mutations in the sinR gene prevent development of competence and motility and the production of growth-related autolysins (Gaur et al 1986;Sekiguchi et al 1988}. It has been shown that its requirement for the development of motility is at the level of motility reguIon gene expression (M. Predich, M. Zelic, and I.…”
mentioning
confidence: 99%
“…B. subtilis AC327 (purl3 his-1 smo-1) (Sekiguchi et al, 1988) was used as the source of chromosomal DNA to construct a I library.…”
Section: Methodsmentioning
confidence: 99%